How should land be used?: bioenergy and responsible innovation in agricultural systems - Mohr, Alison; Shortall, Orla; Helliwell, Richard; Raman, Sujatha (Earthscan (Routledge), 2016)
Bioenergy has been proposed as both a problem and a solution for land use conflicts arising at the nexus between food security and environmental conservation. But such assessments need to be considered in light of differences in the way people value the use of land and the facts that are considered or excluded in making such judgements. While technical and policy appraisals of food security favour a target-based approach that considers land as a global resource to be managed in accordance with universal targets and technological innovation for food production and nature conservation, social researchers highlight the need for a context-based approach where considerations of the role of land in people’s everyday lives and its historical and cultural attachments ought to shape interventions. This Chapter highlights the assumptions and value judgements that underpin different visions of how land should be used by opening up conflicting judgements that arise when we position bioenergy in the context of current and future agricultural systems. We develop a ‘responsible innovation’ framework to highlight the fact that there are multiple pathways for any technological intervention. Drawing on research undertaken in the UK, we apply this framework to valuations of land use and biomass in agricultural systems. We identify a number of, often conflicting, value dimensions related to different uses of land (for food, fuel or fodder), to land quality (should marginal land be used for fuel production) and to different uses of biomass (including competition for the use of straw, the use of biomass for on-farm energy generation as opposed to national energy targets, and biomass for large-scale biorefining to meet multiple objectives at the food/fuel/environment nexus). By opening up to scrutiny the assumptions that reinforce particular innovation pathways we were able to look beyond technical innovation in agricultural systems and land use choices to consideration of social innovations that draw attention to alternative visions of land use in agricultural futures.